HIV-1 Vif and Vpr cooperatively modulate the cell cycle to maximize per-cell virion production - Madison Bandini; Dhaval Ghone; Edward L. Evans; Aussie Suzuki; Nathan M. Sherer (Proceedings of the National Academy of Sciences, 2025)
The HIV type 1 (HIV-1) accessory proteins Virion Infectivity Factor (Vif) and Viral Protein R (Vpr) are essential for efficient virus replication in vivo. Vif mediates degradation of host restriction factor APOBEC3G, while Vpr modulates the host cell proteome in ways that promote virion infectivity and viral gene expression. In cycling cells including CD4+ T cells, Vif and Vpr also severely impact cell cycle progression for reasons that remain unknown. Here, we combined live-cell imaging with virological assays to define the relative impacts of Vif and Vpr on the cell cycle and single-cell virion production. We demonstrate that Vif and Vpr’s effects on the cell cycle are markedly distinct, with Vif arresting cells in mitosis, while Vpr causes a G2 phase delay followed by endoreplication and reversion of cells into a “pseudo-G1” cell state lacking G2 markers. When coexpressed, Vpr’s capacity to bypass mitosis acts to suppress cytotoxicity associated with Vif-mediated cell cycle arrest, with the two proteins cooperating to extend the infected cell’s time in interphase as much as fivefold. Vpr-driven endoreplication also caused duplication of transcriptionally active proviral genomes, yielding a correlative ~twofold increase in per-cell viral gene expression. Based on these findings, we propose that Vif and Vpr coordinately regulate the cell cycle to prolong the infected cell’s lifespan and maximize single-cell virion output.